The Role of Cytokines and Chemokines in Severe Acute Respiratory Syndrome Coronavirus 2 Infections - Hsu, Ren-Jun; Yu, Wei-Chieh; Peng, Guan-Ru; Ye, Chih-Hung; Hu, SuiYun; Chong, Patrick Chun Theng; Yap, Kah Yi; Lee, Jamie Yu Chieh; Lin, Wei-Chen; Yu, Shu-Han (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus (SARS-CoV-2) has as resulted in countless infections and caused millions of deaths since its emergence in 2019. COVID-19-associated mortality is caused by uncontrolled inflammation, aberrant immune function, and a hyperactive and imbalanced cytokine and immune system. The cytokine storm further results in multiple organ failure and lung immunopathology. Therefore, any potential treatments should focus on the direct elimination of virus particles, prevention strategies, and mitigation of immune system imbalance and hyperactivity. This review focuses on cytokine secretions induced by host innate and adaptive immune responses against COVID-19, including interferons, interleukins, tumor necrosis factor alpha, and other chemokines. Furthermore, we discuss potential immunotherapeutic approaches based on relevant pathophysiological features, the systemic immune response against SARS-CoV-2 and data from recent clinical trials and experiments on the COVID-19-associated cytokine storm. Prompt use of these cytokines as diagnostic markers and aggressive prevention and management of the cytokine storm can help determine COVID-19-associated morbidity and mortality. The prophylaxis and rapid management of the cytokine storm appear to significantly improve disease outcomes. Thus, this study aims to provide state-of-the-art information to enable the provision of promising alternative solutions for surviving this pandemic.